Developing brain and behaviour: the role of lipids in infant formula - Dobbing, John (Academic Press, 1997)
Certain long chain polyunsaturated fatty acids (LCPUFAs) are thought to be essential components of the nutrition of infants, including those prematurely born, in the sense that they cannot be synthesises by the immature organism and must therefore be supplied in the diet.